2020
DOI: 10.52943/jikeperawatan.v6i1.365
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kecemasan Pasien Gagal Ginjal Kronik Dalam Menjalani Hemodialisa Di Rumah Sakit Imelda Pekerja Indonesia

Abstract: ABSTRAK   Gagal ginjal kronik merupakan kerusakan ginjal progresif ditandai dengan uremia (urea dan limbah lain yang beredar di dalam darah serta komplikasinya jika tidak di lakukan dialisis atau transplantasi ginjal). Penderita gagal ginjal kronik yang akan melakukan hemodialisa sering mengalami kecemasan. Kecemasan merupakan reaksi normal terhadap situasi yang sangat menekan kehidupan seseorang yang berlangsung tidak lama. Penelitian ini bertujuan untuk mengetahui bagaimana tingkat kecemasan pasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
3
0
8
Order By: Relevance
“…The results of the above study are also following research (Damanik, 2020) which states that most chronic kidney failure patients undergoing hemodialysis experience moderate levels of anxiety. so anxious to see the tubes flowing blood, the costs that must be spent each time undergoing therapy, anxious because invasive procedures will be carried out, the patient still has not accepted the fact that hemodialysis therapy will be lived for the rest of his life, and the uncertainty of recovery.…”
Section: Anxiety Before Being Given Spiritual Mindfulness Based On Br...supporting
confidence: 54%
“…The results of the above study are also following research (Damanik, 2020) which states that most chronic kidney failure patients undergoing hemodialysis experience moderate levels of anxiety. so anxious to see the tubes flowing blood, the costs that must be spent each time undergoing therapy, anxious because invasive procedures will be carried out, the patient still has not accepted the fact that hemodialysis therapy will be lived for the rest of his life, and the uncertainty of recovery.…”
Section: Anxiety Before Being Given Spiritual Mindfulness Based On Br...supporting
confidence: 54%
“…In contrast to the research by Jalante (Jalante, 2020) another factor causing dental caries is brushing teeth. Damanik's (H. Damanik, 2020) other factors that cause dental caries are brushing teeth, and knowledge (H. . The conclusion is that these 7 journals have the same research results, namely there is a relationship between consuming cariogenic foods with the incidence of dental caries in elementary school children.…”
Section: Similarities and Differences Research Articlesmentioning
confidence: 99%
“…Chronic Renal Failure is a clinical condition of progressive and irreversible kidney damage from various causes where there is an incidence of being unable to transport the body's metabolic waste or perform its regular functions (1). The results of Riskesdas in 2018 showed that the pervalence of Chronic Kidney Failure disease in Indonesia ≥ 15 years based on doctor's diagnosis was 19.8% in 2018, an increase compared to the previous year (2).…”
Section: Introductionmentioning
confidence: 99%